ALIMUS - we are feeding!: Study protocol of a multi-center, cluster-randomized controlled trial on the effects of a home garden and nutrition counseling intervention to reduce child undernutrition in rural Burkina Faso and Kenya - Mank, Isabel; Sorgho, Raissa; Zerbo, Fanta; Kagoné, Moubassira; Coulibaly, Boubacar; Oguso, John; Mbata, Michael; Khagayi, Sammy; Muok, Erick M. O.; Sié, Ali; Danquah, Ina (Trials, 2022)
Climate change heavily affects child nutritional status in sub-Saharan Africa. Agricultural and dietary diversification are promising tools to balance agricultural yield losses and nutrient deficits in crops. However, rigorous impact evaluation of such adaptation strategies is lacking. This project will determine the potential of an integrated home gardening and nutrition counseling program as one possible climate change adaptation strategy to improve child health in rural Burkina Faso and Kenya.
Published: 23 May 2022
Gesehen am 01.07.2022